2007
DOI: 10.1097/nen.0b013e318093ece3
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expressions Specifically Detected in Motor Neurons (Dynactin 1, Early Growth Response 3, Acetyl-CoA Transporter, Death Receptor 5, and Cyclin C) Differentially Correlate to Pathologic Markers in Sporadic Amyotrophic Lateral Sclerosis

Abstract: In a differential gene expression profile, we showed previously that dynactin 1 (DCTN1), early growth response 3 (EGR3), acetyl-CoA transporter (ACATN), death receptor 5 (DR5), and cyclin C (CCNC) were prominently up- or downregulated in motor neurons of sporadic amyotrophic lateral sclerosis (ALS). In the present study, we examined the correlation between the expression levels of these genes and the levels of pathologic markers for motor neuron degeneration (i.e. cytoplasmic accumulation of phosphorylated neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…Indeed, dysregulation in either the dynein-dynactin complex (LaMonte et al, 2002;Hafezparast et al, 2003) or peripherin (Beaulieu et al, 1999) causes spinal motor neuron degeneration in mice, presumably through defective axonal transport (LaMonte et al, 2002;Hafezparast et al, 2003;Millecamps et al, 2006). Furthermore, sALS patient spinal motor neurons show decreased levels of dynactin (Jiang et al, 2007). Our human tissue analyses showed that dynein was preferential to hypoglossal and spinal motor neurons in control patient tissues, while in ALS patients dynein was present at similar levels in all motor neuron groups.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, dysregulation in either the dynein-dynactin complex (LaMonte et al, 2002;Hafezparast et al, 2003) or peripherin (Beaulieu et al, 1999) causes spinal motor neuron degeneration in mice, presumably through defective axonal transport (LaMonte et al, 2002;Hafezparast et al, 2003;Millecamps et al, 2006). Furthermore, sALS patient spinal motor neurons show decreased levels of dynactin (Jiang et al, 2007). Our human tissue analyses showed that dynein was preferential to hypoglossal and spinal motor neurons in control patient tissues, while in ALS patients dynein was present at similar levels in all motor neuron groups.…”
Section: Discussionmentioning
confidence: 56%
“…Mutation in Dctn1 gene has been associated to motor neuron degeneration in ALS (Hafezparast et al, 2003) and downregulation of the gene was described in residual motor neurons of postmortem material of ALS patients (Jiang et al, 2007). There is a lack of information on dynactin regulation before clinical onset of ALS despite the fact that dynein-dynactin complex, the only retrograde transport motor, contributes to formation of SOD1 inclusions in the disease (Strom et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, any result obtained with postmortem AD tissue is heavily influenced by the long duration of the disease, which could affect the genetic profile of the tissue. However, it is important to consider that AT-1 was also found upregulated in the motor neurons of ALS patients (Jiang et al, 2007), suggesting a possible involvement in general mechanisms involved with neurodegeneration. In fact, AD and ALS differ at the mechanistic level but share common disease-relevant features, such as disruption of axonal transport, synaptic-cargo impairment, disposal of aberrant protein aggregates and organelle damage (reviewed in De Vos et al, 2008;Wong et al, 2002).…”
Section: At-1 Is Tightly Regulated By the Lipid Second Messenger Ceramentioning
confidence: 99%
“…Recent work has also shown that AT-1 is upregulated in motor neurons of patients affected by sporadic amyotrophic lateral sclerosis (ALS) (Jiang et al, 2007) and mutated in patients affected by autosomal dominant spastic paraplegia-42 (SPG42) (Lin et al, 2008), suggesting an implication in neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%